PENGARUH PEMBASAHAN BERULANG TERHADAP PARAMETER KUAT GESER TANAH LONGSORAN RUAS JALAN TAWAELI – TOBOLI - Setiawan, Hendra (MEKTEK, 2005)
Tawaeli-Toboli road is an arterial road together with the trans sulawesi road which has an important function in transportation of central sulawesi. Landslide disaster and slope failure which frequently occur in the rainy season is the main problems in this road. Tawaeli-Toboli road traverses a complicated terrain formed by mountain ranges with steep slope angle. The influence of rewetting processed on soil shear strength were done by direct shear test. The results showed that rewetting processed able to decrease soil shear strength